(untitled) (Scripta : English Department Journal, 2022)
The purpose of this study is to determine how effectively the Listen English Practice App at SMP Islam Ruhama improves students’ understanding of listening. The population of this research is eight²-grade students, and the sample is 27 students. The method of this study is experimental research with a pre-experimental design that applies the pre-test and post-test. In this study, the researcher used one class as an experiment. Data has been analyzed using a t-test, data analysis shows the average value of the pre-test is 51.29 and the post-test is 80.74. Interpretation of data shows that there are some significant differences between listening skills using Listen English Practice App and not using Listen English Practice App. This shows that the Listen English Practice App is influential for eight²-grade students junior high school students of SMP Islam Ruhama. An option in learning media is the Listen English Practice Application; it has a positive impact on the research and can encourage students to study English.